Polymer‐Coated Radioluminescent Nanoparticles for Quantitative Imaging of Drug Delivery. (22nd July 2014) - Moore, Thomas L.; Wang, Fenglin; Chen, Hongyu; Grimes, Stuart W.; Anker, Jeffrey N.; Alexis, Frank
<x xml:space="preserve">Abstract</x> Some theranostic nanoparticle (NP) drug delivery systems are capable of measuring drug release rates in situ. This can provide quantitative information regarding drug biodistribution, and drug dose that is delivered to cells or tissues. Here, X‐ray excited optical luminescent (XEOL) NPs coated with poly(glycolide)‐poly(ethylene glycol) (XGP) are used measure the amount of drug released into cells. The photoactive drug protoporphyrin IX (PpIX) is loaded into XGP and is able to attenuate the XEOL NP emission. Measuring an increase in XEOL intensity as PpIX is released enables the measurement of drug release into glioblastoma cells (GBM). Biodistribution studies in a BALB/c mouse GBM intracranial xenograft model show significant XGP accumulation at the site of the GBM xenograft within the brain, and not in adjacent healthy brain tissues. There is no uptake of XGP in the heart or kidneys, the primary organs associated with drug and gadolinium ion toxicity. NP toxicity is tested with U‐138MG GBM in vitro, and NPs show low cytotoxicity at concentrations of 100 μg/mL. In vivo dose escalation studies in BALB/c mice show no adverse effects at doses up to 75 mg/kg. These theranostic NPs offer an approach to quantitatively measure drug release into cells.